East Indian Sandalwood Oil Is a Phosphodiesterase Inhibitor: A New Therapeutic Option in the Treatment of Inflammatory Skin Disease - Sharma, Manju; Levenson, Corey; Browning, John C.; Becker, Emily M.; Clements, Ian; Castella, Paul; Cox, Michael E. (Frontiers in Pharmacology, 2018)
Cyclic adenosine monophosphate phosphodiesterases (PDEs) regulate pro-inflammatory cytokine production. One isoform, PDE4, is overactive in chronic relapsing inflammatory skin diseases: psoriasis and eczema/atopic dermatitis, and in several cancers. East Indian sandalwood oil (EISO) has significant anti-inflammatory properties. Here, we report that 75% of pediatric eczema/atopic dermatitis patients treated with topical EISO formulations achieved a >50% reduction in their Eczema Area and Severity Index score. EISO treatment of a psoriasis model reduced PDE4 expression and reversed histopathology. EISO directly inhibited PDE enzymatic activity in vitro. In lipopolysaccharide-stimulated human dermal fibroblast, BEAS-2B, A549 and THP-1 cells, EISO suppressed total cellular PDE activity, PDE4 and 7 transcript levels, nuclear factor kappa B (NF-κB) activation, and pro-inflammatory cytokines/chemokine production. These results suggest that EISO anti-inflammatory activity is mediated through suppressing PDE activity, thus facilitating cAMP-regulated inhibition of NF-κB and indicate EISO as an attractive natural therapeutic for chronic and acute inflammatory disorders.